Sustainable thinking toward to industry's future combined with new knowledge on greenhouse effect mitigation generated by the grinding process - Lopes, José Claudio [UNESP]; Carvalho, Guilherme Antonio de [UNESP]; Moretti, Guilherme Bressan [UNESP]; Ávila, Benício Nacif [UNESP]; Rodrigues, Matheus de Souza [UNESP]; Garcia, Mateus Vinícius [UNESP]; Ribeiro, Fernando Sabino Fonteque; Rodrigues, Alessandro Roger; Sanchez, Luiz Eduardo de Angelo [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Elsevier, 2023)
Grinding is a machining process applied in the manufacture of components that require an excellent surface finish and high geometric and dimensional precision, being applied in the final stages of component manufacturing. Due to its high heat generation, grinding needs adequate lubrication and cooling methods, aiming to meet the demands of the ground component as well as to mitigate the environmental impacts resulting from the application of cutting fluids. Allied with this, the growing demand for new materials, such as advanced ceramics, has become a new challenge for grinding. In addition to being chemically and thermally stable, advanced ceramics are highly resistant to wear, making grinding this type of material difficult. Traditionally, cutting fluids have alkanolamines, nitrosamines, volatile organic compounds, mineral oils, hydrocarbons and heavy metals in their composition. Thus requiring proper disposal to inhibit groundwater and soil contamination, reducing immediate and long-term damage to the planet and society. That said, it is extremely important that scientific and technological advances in machining processes, especially grinding, allow for cleaner machining through techniques that reduce the need to apply large volumes of cutting fluid. In this sense, the minimum quantity lubrication technique (MQL) consists of applying a small amount of oil through a jet of compressed air, achieving results similar to the flood method in many cases. However, the lower cooling capacity of MQL is an obstacle to overcome. Thus, this work analyzed advanced grinding ceramics using a diamond grinding wheel combined with a new technology responsible for cleaning the grinding wheel (WCJ) under four different angles (0°, 30°, 60° and 90°). Surface roughness, roundness error, diametral wear of the grinding wheel, G ratio, grinding power, grinding cost analysis, and pollutant CO2 emissions involving each application were evaluated. As a result, the flood lubri-refrigeration method showed the best performance in roughness and surface roundness error values. However, the MQL + WCJ 30° presented similar results about the flooding method, proving competitive for industrial use. Furthermore, MQL applications led to lower CO2 pollution values than the flood method, making it a great green alternative for the environment.
Keywords: Advanced ceramic; Cutting fluid; Environment; Grinding; MQL